Databases and information systems : 13th International Baltic Conference, DB&IS 2018, Trakai, Lithuania, July 1-4, 2018, Proceedings /: 13th International Baltic Conference, DB&IS 2018, Trakai, Lithuania, July 1-4, 2018, Proceedings. (2018) - Unknown
No abstract available